Millennial social entrepreneurial intent and social entrepreneurial self-efficacy: a comparative entrepreneurship study. Issue 1 (11th February 2021) - Zhang, Yang; Trusty, Juanita; Goroshnikova, Tatiana; Kelly, Louise; Kwong, Kwok K.; McGuire, Stephen J.J.; Perusquia, Juan; Prabhu, Veena P.; Shen, Minghao; Tang, Robert
Abstract : Purpose: The purpose of this study is to propose and test predictors of millennials' social entrepreneurial intent (SEI), mediating mechanisms and influential contextual factors. Design/methodology/approach: This study includes survey data from 1, 890 respondents, 315 each from China, Mexico, Nigeria, Philippines, Russia and the USA. Findings: Empirical results show that social entrepreneurial self-efficacy (SESE) mediated the relationship between perseverance and proactive personality and the dependent variable SEI in all six countries. Life satisfaction positively moderated this relationship among US students and negatively moderated it among Chinese students. In China dissatisfaction appears to enhance SEI, while in the US satisfaction appears to do so. Originality/value: This paper identifies the mediating role of SESE and the moderating role of life satisfaction when explaining SEI, as well as providing data from millennials in six countries.